2010
DOI: 10.1111/j.1365-2265.2010.03904.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulse methylprednisolone and oral methylprednisolone treatments on serum levels of oxidative stress markers in Graves’ ophthalmopathy

Abstract: Oxidative stress appears to be involved in the pathophysiology of GO. Relative to oral dosing, the intravenous administration of a glucocorticoid seems to yield more rapid improvement in disease activity. MDA might be useful as an indicator of clinical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 32 publications
2
42
1
Order By: Relevance
“…Recently, Akarsu et al [43] further evaluated the relationship between GO and the effect of GC therapy (intravenous vs. oral) on serum of MDA and GSH. The study group included 33 recently diagnosed euthyroid GD patients with moderately severe and active GO, 20 euthyroid GD patients without GO, and 15 healthy controls.…”
Section: Oxidative Stress and Graves’ Orbitopathymentioning
confidence: 99%
“…Recently, Akarsu et al [43] further evaluated the relationship between GO and the effect of GC therapy (intravenous vs. oral) on serum of MDA and GSH. The study group included 33 recently diagnosed euthyroid GD patients with moderately severe and active GO, 20 euthyroid GD patients without GO, and 15 healthy controls.…”
Section: Oxidative Stress and Graves’ Orbitopathymentioning
confidence: 99%
“…Therefore, thyroid hormone administration to vertebrates leads to an accelerated basal metabolic rate and oxygen consumption in the target tissues [1]. Both clinical [2,3] and experimental [1,4,5] studies have demonstrated that hyperthyroidism can cause an elevation in oxidative stress, most likely because of increased mitochondrial oxygen consumption. Mitochondria are the main production site of free oxygen radicals in healthy tissues because the leak of these radicals from the mitochondrial respiratory chain and the free oxygen radical production rate can be directly related to the rate of mitochondrial oxygen consumption [6].…”
Section: Introductionmentioning
confidence: 99%
“…The superoxide (O 2 .-), hydroxyl (HO), perhydroxyl radicals (HO 2 -) and nitric oxide (NO) are the most important free radicals that are derived from oxygen [7]. If not immediately neutralized, O 2 -radicals are converted to other reactive oxygen species (ROS), such as the HO radical and H 2 O 2 , by a classical Fenton reaction in the presence of iron. Because of their high reactivity and non-specific nature, ROS can attack almost all biomolecules present in their vicinity, including membrane lipids, causing oxidative stress in cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic methylprednisolone administration has been shown to induce rat lens opacity (19) . The protective effect of methylprednisolone against oxidative injury has been found in several disease types (20)(21)(22)(23)(24) . However, no studies in the literature have related the impact of systemic methylprednisolone to the oxidative stress of crystalline lenses.…”
Section: Discussionmentioning
confidence: 99%